eSPEM - A SPEM Extension for Enactable Behavior Modeling - Ellner, Ralf; Al-Hilank, Samir; Drexler, Johannes; Jung, Martin; Kips, Detlef; Philippsen, Michael (6th European Conference of Modelling Foundations and Applications, 2010)
OMG's SPEM - by means of its (semi-)formal notation - allows for a detailed description of development processes and methodologies, but can only be used for a rather coarse description of their behavior. Concepts for a more fine-grained behavior model are considered out of scope of the SPEM standard and have to be provided by other standards like BPDM/BPMN or UML. However, a coarse granularity of the behavior model often impedes a computer-aided enactment of a process model. Therefore, in this paper we present eSPEM, an extension of SPEM, that is based on the UML meta-model and focused on fine-grained behavior and life-cycle modeling and thereby supports automated enactment of development processes. © 2010 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD2.espema